EL PROBLEMA DE LA JUSTIFICACIÓN EPISTÉMICA DE SISTEMAS NORMATIVOS: UNA APROXIMACIÓN ENTRE COHERENTISMO Y NORMATIVISMO (2016)
This article is a result of the investigation project “conceptual precisions on the normativist legal theory”. In the present work it is made a characterization of Kelsen normativist proposal as a form of epistemic coherentism. For that I analysed the problem of epistemic justification and the conflict between fundacionist and coherentist; then it is analysed Kelsen’s works in there context to specify three points which could in conclusion identify Kelsen as a moderate coherentist.